Legacies: Collecting America's History at the Smithsonian - Lubar, Steven and Kendrick, Kathleen M. (Washington, D.C. Smithsonian Institution Press in association with the National Museum of American History, 2001)
The Smithsonian Institution has been America's museum since 1846. What do its vast collections -- from the ruby slippers to a piece of Plymouth Rock, first ladies' gowns to patchwork quilts, a Model T Ford to a customized Ford LTD low rider -- tell Americans about themselves? In this lavishly illustrated guide to the Smithsonian's National Museum of American History, Steven Lubar and Kathleen M. Kendrick tell the stories behind more than 250 of the museum's treasures, many of them never before photographed for publication. These stories not only reveal what America as a nation has decided to save and why but also speak to changing visions of national identity.
Includes Colored Ilustrarions and Index
Keywords: United States -- Civilization